2012
DOI: 10.1073/pnas.1204991109
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into triple-helical collagen cleavage by matrix metalloproteinase 1

Abstract: Collagenases of the matrix metalloproteinase (MMP) family play major roles in morphogenesis, tissue repair, and human diseases, but how they recognize and cleave the collagen triple helix is not fully understood. Here, we report temperature-dependent binding of a catalytically inactive MMP-1 mutant (E200A) to collagen through the cooperative action of its catalytic and hemopexin domains. Contact between the two molecules was mapped by screening the Collagen Toolkit peptide library and by hydrogen/deuterium exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
316
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(327 citation statements)
references
References 50 publications
8
316
3
Order By: Relevance
“…2B shows that the reaction with the triple-helical substrate induced an increase in fluorescence for 30 ms, which decayed exponentially until ∼400 ms, whereas the fluorescence after the reaction with the single-stranded substrate increased until 70 ms and then exponentially decreased until reaching steady state at ∼400 ms. These results are in line with previously reported analyses, suggesting that conformational changes of MT1-MMP take place during Michaelis complex formation for triple-helical collagen model peptides (24,25). The net change in tryptophan fluorescence (Fig.…”
Section: Structural Conformational Transitions During Turnover Equilisupporting
confidence: 82%
See 1 more Smart Citation
“…2B shows that the reaction with the triple-helical substrate induced an increase in fluorescence for 30 ms, which decayed exponentially until ∼400 ms, whereas the fluorescence after the reaction with the single-stranded substrate increased until 70 ms and then exponentially decreased until reaching steady state at ∼400 ms. These results are in line with previously reported analyses, suggesting that conformational changes of MT1-MMP take place during Michaelis complex formation for triple-helical collagen model peptides (24,25). The net change in tryptophan fluorescence (Fig.…”
Section: Structural Conformational Transitions During Turnover Equilisupporting
confidence: 82%
“…degradation involves major conformational rearrangements of both enzyme and substrate to facilitate binding and catalysis (24,25). Therefore, we chose to study the role of solvation dynamics in more complex enzymatic reactions, such as the enzymatic degradation of collagen-and gelatin-like substrates by MT1-MMP, by our established X-ray-and THz-based integrated spectroscopic approach (Fig.…”
Section: Significancementioning
confidence: 99%
“…Human collagenases, such as MMP-1 and MMP-13, cleave between Gly 775 and Leu 776 and divide collagen chains into 1 ⁄ 4 and 3 ⁄ 4 fragments (42,43). A recent study indicated that Leu residues at positions 776 and 785 were critical for MMP activity through direct interaction with the MMP catalytic and hemopexin domains, respectively (44). Because the minimum Fn binding sequence defined here overlaps with the key residues for MMP cleavage, MMP and Fn could compete for binding at this site.…”
Section: Discussionmentioning
confidence: 99%
“…Collagenolytic proteases, such as MCP-01 (30, 42) and MMP-1, -8, and -13 (49,50), usually have a C-terminal domain that functions as a collagen-binding domain to mediate and facilitate collagen hydrolysis by the enzyme. However, there are also some collagenolytic proteases that do not need an additional domain for collagenolysis, such as MMP-12 (51) and the serine proteases from fiddler crab (16,18).…”
Section: Discussionmentioning
confidence: 99%